αSynuclein control of mitochondrial homeostasis in human-derived neurons is disrupted by mutations associated with Parkinson's disease - Pozo Devoto, Victorio Martin; Dimopoulos, Nicolas; Alloatti, Matías; Pardi, María Belén; Saez, Trinidad M; Otero, María Gabriela; Cromberg, Lucas Eneas; Marín-Burgin, Antonia; Scassa, Maria Elida; Stokin, Gorazd B; Schinder, Alejandro F; Sevlever, Gustavo; et al. (Scientific reports, 2017)
The etiology of Parkinson's disease (PD) converges on a common pathogenic pathway of mitochondrial defects in which α-Synuclein (αSyn) is thought to play a role. However, the mechanisms by which αSyn and its disease-associated allelic variants cause mitochondrial dysfunction remain unknown. Here, we analyzed mitochondrial axonal transport and morphology in human-derived neurons overexpressing wild-type (WT) αSyn or the mutated variants A30P or A53T, which are known to have differential lipid affinities. A53T αSyn was enriched in mitochondrial fractions, inducing significant mitochondrial transport defects and fragmentation, while milder defects were elicited by WT and A30P. We found that αSyn-mediated mitochondrial fragmentation was linked to expression levels in WT and A53T variants. Targeted delivery of WT and A53T αSyn to the outer mitochondrial membrane further increased fragmentation, whereas A30P did not. Genomic editing to disrupt the N-terminal domain of αSyn, which is important for membrane association, resulted in mitochondrial elongation without changes in fusion-fission protein levels, suggesting that αSyn plays a direct physiological role in mitochondrial size maintenance. Thus, we demonstrate that the association of αSyn with the mitochondria, which is modulated by protein mutation and dosage, influences mitochondrial transport and morphology, highlighting its relevance in a common pathway impaired in PD.
Keywords: Neurons; Mutant Proteins; lidské embryonální kmenové buňky; mitochondrie; velikost organel; Axonal Transport; Protein Domains; Parkinsonova nemoc; Humans; homeostáza; mitochondriální membrány; alpha-Synuclein; neurony; Organelle Size; Parkinson Disease; Human Embryonic Stem Cells; alfa-synuklein; Mitochondria; axonální transport; Homeostasis; mutantní proteiny; proteinové domény; Mitochondrial Membranes; lidé